Phenolic compounds profile and antioxidant activity of pea (Pisum sativum L.) and black bean (Phaseolus vulgaris L.) sprouts - Borges-Martínez,Eduardo (2022)
Abstract Germination increases total phenolic compounds (TF) concentration and antioxidant activity (AOx). The characterization and quantification of TPC, total flavonoids content (TPC), and AOx of beans (Phaseolus vulgaris) and peas (Pisum sativum) sprouts, germinated for ten days was performed. Results showed that the highest concentration of TPC for both sprouts was in days 6 and 7 (685.21 and 910.69 mg GAE/100 g dry matter) and TF varied only for beans. AOx of the pea sprouts was 512.64 and 6083.55 mg ET/100 g dry matter to DPPH and ORAC method, respectively, is higher than for bean. Regarding FRAP, bean sprouts showed better values (421.07 mg ET/100 g dry matter) compared to pea; in the CUPRAC analysis, sprouted bean showed better activity than a pea (85.76 and 44.05% inhibition). Germination induced variations in gallic and syringic acids in pea sprouts and of catechin and quercetin in the bean. Germination time and legume type are important factors the biological activity of sprouts.